2023
DOI: 10.1101/2023.09.15.557864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the environmental impacts of conventional and organic scenarios of rainbow trout farming in France

Simon Pouil,
Mathieu Besson,
Florence Phocas
et al.

Abstract: In France, rainbow trout (Oncorhynchus mykiss) farming traditionally used flow-through systems, which raised concerns about environmental impacts, including limited freshwater availability, and the use of ingredients from intensive agriculture and fishing. To address the growing demand for sustainable food products, there is an increasing interest in organic aquaculture. In this study, we employed an attributional life cycle assessment (LCA) to analyse the environmental impacts of rainbow trout production. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…According to Pouil (2023) [35] , organic farming has numerous advantages, such as better soil and water quality, increased biodiversity, and environmental conservation. Research has demonstrated that organic farming encourages just interactions and a high standard of living for every individual involved.…”
Section: "Pag Chemical Mas Napapadali Yung Pag Aani At Nababantayan N...mentioning
confidence: 99%
“…According to Pouil (2023) [35] , organic farming has numerous advantages, such as better soil and water quality, increased biodiversity, and environmental conservation. Research has demonstrated that organic farming encourages just interactions and a high standard of living for every individual involved.…”
Section: "Pag Chemical Mas Napapadali Yung Pag Aani At Nababantayan N...mentioning
confidence: 99%